2004
DOI: 10.1128/aem.70.11.6905-6908.2004
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Laser Ablation of Natural Marine Biofilms

Abstract: We studied the efficiency of pulsed low-power laser irradiation of 532 nm from an Nd:YAG (neodymiumdoped yttrium-aluminum-garnet) laser to remove marine biofilm developed on titanium and glass coupons. Natural biofilms with thicknesses of 79.4 ؎ 27.8 m (titanium) and 107.4 ؎ 28.5 m (glass) were completely disrupted by 30 s of laser irradiation (fluence, 0.1 J/cm 2 ). Laser irradiation significantly reduced the number of diatoms and bacteria in the biofilm (paired t test; P < 0.05). The removal was better on ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…In any case, the laser radiation in the visible area was found to be a promising tool for the removal of biofilms from the surfaces and might be useful in many industrial uses such as dental application or the treatment of ballast water tanks, for example. This observation agrees with earlier studies (Nandakumar et al, 2004a). To conclude, in suspended culture of Moraxella strain UV radiation resulted in a higher killing rate than by the visible laser light.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In any case, the laser radiation in the visible area was found to be a promising tool for the removal of biofilms from the surfaces and might be useful in many industrial uses such as dental application or the treatment of ballast water tanks, for example. This observation agrees with earlier studies (Nandakumar et al, 2004a). To conclude, in suspended culture of Moraxella strain UV radiation resulted in a higher killing rate than by the visible laser light.…”
Section: Discussionsupporting
confidence: 93%
“…Ever since the invention of the laser (Maiman, 1960), its ability to kill bacteria has been explored and practiced (Wilson, 1993;Deckelbaum, 1994). Recently, the ability of visible laser radiation (532 nm) to remove marine and single species biofilms formed on the experimental surfaces has been studied (Nandakumar et al, 2004a). Additionally, reports are also available on the possibility of using visible laser light as an antifouling tool, that is, to kill the larvae of biofouling organisms (Nandakumar et al, 2003b).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…(Nichols et al 2004;Park et al 2005;Evans et al 2007;Nam et al 2007). Such studies have focused on the isolation of Pseudoalteromonas from diverse habitats, its biopolymer (including EPS) production and biofilm formation (Nichols et al 2004;Nandakumar et al 2004). Recently, Nichols et al (2004) isolated bacteria belonging to the Pseudoalteromonas from Antarctic waters and studied EPS production in batch cultures.…”
Section: S Rrna Sequence and Phylogenetic Analysismentioning
confidence: 98%
“…Some of these types of irradiations are used in the treatment of diseases and sterilization of surgical tools (Deckelbaum 1994). On the other hand, recent studies have shown that laser irradiation can be used as a tool to remove biofilms formed on solid surfaces (Nandakumar et al. 2002b, 2004a,b).…”
Section: Introductionmentioning
confidence: 99%